NYONGKOLAN BETWEEN TRADITION AND MODERNITY: CULTURAL ACCULTURATION ANALYSIS ACCORDING TO ROBERT REDFIELD'S PERSPECTIVE - Ahmad Gautsul Anam; Junaidi (GEMOVE: Journal of Gender, Movement, and Empowerment, 2025)
This study examines the Nyongkolan tradition of Sasak society in Lombok through the lens of Robert Redfield's cultural acculturation theory, employing a multidisciplinary approach that integrates legal and inclusive perspectives. Nyongkolan, a ceremonial wedding procession characterized by mass participation and festive atmosphere, represents a complex intersection of traditional values and modern influences. Using a literature review methodology, this research analyzes how Nyongkolan demonstrates cultural transformation while maintaining its essential identity, explores the legal frameworks governing this tradition in contemporary Indonesia, and evaluates its role in promoting social inclusion across diverse community segments. Findings reveal that Nyongkolan exemplifies Redfield's concept of the folk-urban continuum, where traditional practices adapt to urban modernity without losing core cultural significance. The tradition simultaneously faces challenges from modernization pressures and legal regulations while demonstrating remarkable resilience through adaptive strategies. From an inclusive perspective, Nyongkolan functions as a social leveler that transcends economic and social boundaries, though gender dynamics and accessibility issues require ongoing attention. This study contributes to understanding how indigenous traditions negotiate modernity while preserving cultural authenticity and promoting social cohesion in Indonesia's pluralistic society.